2007
DOI: 10.1128/jvi.02205-06
|View full text |Cite
|
Sign up to set email alerts
|

Polybasic KKR Motif in the Cytoplasmic Tail of Nipah Virus Fusion Protein Modulates Membrane Fusion by Inside-Out Signaling

Abstract: The cytoplasmic tails of the envelope proteins from multiple viruses are known to contain determinants that affect their fusogenic capacities. Here we report that specific residues in the cytoplasmic tail of the Nipah virus fusion protein (NiV-F) modulate its fusogenic activity. Truncation of the cytoplasmic tail of NiV-F greatly inhibited cell-cell fusion. Deletion and alanine scan analysis identified a tribasic KKR motif in the membraneadjacent region as important for modulating cell-cell fusion. The K1A mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
185
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(205 citation statements)
references
References 73 publications
(103 reference statements)
16
185
0
Order By: Relevance
“…Henipavirus, like many paramyxoviruses, requires the presence of two surface glycoproteins for virus-cell and cell-cell fusion (8,9,36): the fusion protein, F, which mediates the membrane fusion event, and the attachment protein, G, which binds cellular receptors ephrin B2 (6,22) and ephrin B3 (23) and which is required for F-mediated membrane fusion. Interactions between the fusion and attachment proteins of a number of paramyxoviruses have been observed previously (30,33,35), and interactions between the henipavirus F and G proteins have been demonstrated by coimmunoprecipitation (1)(2)(3)(4)(5)18). However, important questions remain concerning the timing of these interactions and the mechanism by which the attachment protein regulates F-mediated fusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Henipavirus, like many paramyxoviruses, requires the presence of two surface glycoproteins for virus-cell and cell-cell fusion (8,9,36): the fusion protein, F, which mediates the membrane fusion event, and the attachment protein, G, which binds cellular receptors ephrin B2 (6,22) and ephrin B3 (23) and which is required for F-mediated membrane fusion. Interactions between the fusion and attachment proteins of a number of paramyxoviruses have been observed previously (30,33,35), and interactions between the henipavirus F and G proteins have been demonstrated by coimmunoprecipitation (1)(2)(3)(4)(5)18). However, important questions remain concerning the timing of these interactions and the mechanism by which the attachment protein regulates F-mediated fusion.…”
mentioning
confidence: 99%
“…An alternative model for paramyxovirus fusion has suggested that attachment proteinfusion protein interactions occur only after the attachment protein binds the receptor. However, analysis of henipavirus G and F mutants suggests that F-G avidity inversely correlates with fusion (2,3,5), and Hendra virus G protein mutants deficient in receptor binding also lose the ability to coimmu- FIG. 3.…”
mentioning
confidence: 99%
“…The cytoplasmic domain has been implicated in the fusion activity of some paramyxovirus F proteins, since mutations in the CT domain or extensions of this domain can affect fusion activity (1,5,52,63,66). The role of the TM domain in the structure and function of paramyxovirus F proteins has not, however, been extensively investigated.…”
mentioning
confidence: 99%
“…The cytoplasmic tails of viral fusion proteins have also been implicated in fusion activity in several studies, and many mutations have been identified that reduce fusion activity (1,16,38,44). For PIV5 F, deletion of the cytoplasmic tail impairs fusion pore enlargement (16), and increasing the length of the cytoplasmic tail such that it has the propensity to form a three-helix bundle abolishes fusion (48).…”
mentioning
confidence: 99%